Communication and Power Engineering - Rajesh, R; Mathivanan, B (Walter de Gruyter GmbH, 2016)
Communication and Power Engineering are the proceedings of the joint International conferences organized by IDES in the year 2016.The aim of these conference proceedings is to bringing together the researchers, scientists, engineers, and scholar students in all areas of Computer Science, Power Engineering, Electrical & Electronics and provides an.